2017
DOI: 10.1371/journal.pone.0186591
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breast reduction surgery on breastfeeding: Systematic review of observational studies

Abstract: BackgroundAlmost half a million breast reduction surgeries are performed internationally each year, yet it is unclear how this type of surgery impacts breastfeeding. This is particularly important given the benefits of breastfeeding.ObjectivesTo determine if breast reduction surgery impacts breastfeeding success and whether different surgical techniques differentially impact breast feeding success.MethodsDatabases were searched up to September 5, 2017. Studies were included if they reported the number of women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 57 publications
0
34
0
3
Order By: Relevance
“…The decision-making of these women was limited, in which most of them disregarded the effects of mammoplasty on breastfeeding, facing doubts and/or questions only years after the surgery when they became pregnant (1,21) . In the conceptual framework of the theory, organizational systems of protection, promotion and support are related to other previously discussed elements, emerging as compensation resources to deal with the constraints arising from inadequate biological conditions for breastfeeding (9) .…”
Section: Discussionmentioning
confidence: 99%
“…The decision-making of these women was limited, in which most of them disregarded the effects of mammoplasty on breastfeeding, facing doubts and/or questions only years after the surgery when they became pregnant (1,21) . In the conceptual framework of the theory, organizational systems of protection, promotion and support are related to other previously discussed elements, emerging as compensation resources to deal with the constraints arising from inadequate biological conditions for breastfeeding (9) .…”
Section: Discussionmentioning
confidence: 99%
“…e Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines were used [5]. In addition, the methods followed in this review were similar to the methods in Kraut et al 2017 systematic review [6].…”
Section: Methodsmentioning
confidence: 99%
“…When performing the procedure, certain surgical techniques are used to maintain breastfeeding capacity. It seems that preserving the subarachnoid parenchyma increases the subsequent chances of breastfeeding, when the subarachnoid parenchyma was not kept, only 4% of women were able to breastfeed 35 . Some studies have shown that women following reduction mammoplasty discontinued exclusive breastfeeding after an average duration of only 5 days and had an exclusively breastfeeding rate at 4 months after birth of 4% compared to control 22% 36 .…”
Section: Breast Augmentation and Reduction Mammoplastymentioning
confidence: 99%